A Gendered Study Exploring Politeness Strategies on Social Media: case of Algerian Youth (Revue El-Wahat pour les Recherches et les Etudes, 2025)
Language is subject to variation across individuals due to its dynamic nature. Among the key dimensions influencing linguistic variation is gender, with males and females often exhibiting distinct patterns of language use. Thus, one noticeable area where this variation emerges is in the expression of politeness. This study aims to explore gendered differences in the use of politeness strategies on social media, focusing specifically on Algerian youth. To investigate this phenomenon, a mixed-method approach was employed within a case study framework using a questionnaire and an interview to collect necessary data. The findings serve as evidence that gender plays a significant role in shaping online politeness strategies. While both genders strive to be polite, women tend to employ more overt expressions of politeness, whereas men often adopt more indirect or subtle forms. These findings reinforce the notion that gender-based linguistic variation is a persistent sociolinguistic reality, manifesting not only in offline communication but also within digital spaces.